2007
DOI: 10.1038/sj.npp.1301562
|View full text |Cite
|
Sign up to set email alerts
|

AMPA Receptor Potentiation can Prevent Ethanol-Induced Intoxication

Abstract: We present a substantial series of behavioral and imaging experiments, which demonstrate, for the first time, that increasing AMPA receptor-mediated neurotransmission via administration of potent and selective biarylsulfonamide AMPA potentiators LY404187 and LY451395 reverses the central effects of an acutely intoxicating dose of ethanol in the rat. Using pharmacological magnetic resonance imaging (phMRI), we observed that LY404187 attenuated ethanol-induced reductions in blood oxygenation level dependent (BOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The mechanisms of kainate receptor regulation during alcoholism and other forms of synaptic plasticity is far less understood than AMPA or NMDA regulation. Previous studies have indicated that the intoxicating and reinforcing effects of ethanol are mediated in part by the effects on AMPA and kainate receptors (Valenzuela and Cardoso, 1999; Backstrom and Hyytia, 2004; Sanchis-Segura et al, 2006; Jones et al, 2008; Stuber et al, 2008). For example, acute ethanol decreases AMPA and kainate receptor-mediated currents in a variety of limbic brain regions (Weiner et al, 1999; Crowder et al, 2002; Carta et al, 2003; Moykkynen et al, 2003; Stuber et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of kainate receptor regulation during alcoholism and other forms of synaptic plasticity is far less understood than AMPA or NMDA regulation. Previous studies have indicated that the intoxicating and reinforcing effects of ethanol are mediated in part by the effects on AMPA and kainate receptors (Valenzuela and Cardoso, 1999; Backstrom and Hyytia, 2004; Sanchis-Segura et al, 2006; Jones et al, 2008; Stuber et al, 2008). For example, acute ethanol decreases AMPA and kainate receptor-mediated currents in a variety of limbic brain regions (Weiner et al, 1999; Crowder et al, 2002; Carta et al, 2003; Moykkynen et al, 2003; Stuber et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…LY404187 and LY451395, both selective biarylsulfonaminde AMPA agonists, were found to reverse the acute intoxication induced by alcohol consumption. In addition, both compounds significantly reversed the loss of motor coordination and operant task disruption induced by ethanol (Jones et al, 2008). Thus, AMPA receptor antagonists may have an important role as a possible therapeutic compounds for managing acute ethanol intoxication (Jones et al, 2008).…”
Section: Glutamate Receptors In Audmentioning
confidence: 99%
“…120 In a rodent model of acute alcohol administration, an ampakine (LY404187) reversed the effects of acute ethanol intoxication on locomotor and operant behavior, and on brain activity (reversed decreases in blood oxygen level-dependent magnetic resonance signal after 0.6 g kg −1 ethanol and attenuated the decreases in glucose metabolism after 2.0 g kg −1 ethanol). 121 Common among these three studies is the inhibition of some effects associated with the acute drug administration, thereby posing ampakines as potential treatments for acute intoxication in emergency room settings. Ampakines also have neuroprotective effects, which are mediated in part by inducing BDNF, and LY503430 and LY404187 were neuroprotective in an animal model of Parkinson’s disease (6-hydroxydopamine and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) toxicity), even when the treatment was delayed for 14 days after the lesion was established.…”
Section: Potential Targets For Restoring Cortico-accumbens Plasticitymentioning
confidence: 99%